Entrepreneurship education in Islamic perspective - Asror, Fuad Mafatichul; Santosa, Sedya (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
This study aims to determine Entrepreneurship Education in an Islamic Perspective using a descriptive qualitative approach and reviewed using the library research method exploring the data to become a complete research result. Entrepreneurship education is a program that includes teaching about what an entrepreneur should do in the face of the fast pace of this world in the field of trade with increasingly fierce competition. The cultivation of entrepreneurial values develops into the world of education intending to form a complete human being. The Islamic perspective on entrepreneurship education is not far from the story of the Prophet Muhammad SAW. He can be a role model in entrepreneurship in an honest, trustworthy, and strong spirit in trading. Entrepreneurship education is important because the advancement of science in technology also greatly affects entrepreneurship in the21st century, where trade in the digital world has advanced rapidly. Hence, it takes an entrepreneur who is proficient in technology to keep up with the times. Therefore, entrepreneurship education is owned by an entrepreneur and must be applied to start from elementary school education to tertiary education to build the younger generation's soul and reduce unemployment in Indonesia while still implementing good Islamic entrepreneurship.